Study on optimization of Al6061 sphere surface roughness in diamond turning based on central composite design model and grey wolf optimizer algorithms - Le Thanh Binh; Duong Xuan Bien; Ngo Viet Hung; Chu Anh My; Hoang Nghia Duc; Nguyen Kim Hung; Bui Kim Hoa (Tạp chí Khoa học và Công nghệ)
This paper presents optimization results of the Al6061 surface roughness in turning ultra-precision based on the central composite design method (CCD) and the grey wolf optimization algorithm (GWO). The experimental matrix is built with three independent variables including spindle speed, feed rate and depth of cut. With the experimental data, the roughness regression model is established. The ANOVA module is used to evaluate the quality of the regression model. The GWO algorithm is used to optimize the roughness within the range of pre-determined cutting conditions. The most reasonable cutting parameter set is found to ensure that the surface roughness of the Al6061 material reaches the smallest value. The influence of parameter pairs on the roughness is analyzed specifically. The research results are of great significance in improving the surface quality of Al6061 material in turning ultra-precision.